Null Biminimal General Helices in the Lorentzian Heisenberg Group - Turhan, Essin; Korpinar, Talat (Chiang Mai Univ, Fac Science, 2011)
In this paper, we study null biminimal curve in the Lorentzian Heisenberg group Heis(3). We characterize non-geodesic null biminimal general helix in terms of its curvatures and torsions in the Lorentzzian Heisenberg group Heis(3).
Keywords: Heisenberg group; Biminimal curve; General helix